Assessing the Financial Impact of Exchange Rate Movements on Profit Reporting: A Case Study of KDB Bank Uzbekistan - Sodikov Ulugbek Gulomjon Ugli; Denny Andriana; R. Nelly Nur Apandi; Xoshimov Doniyor (Tazkia Islamic University College, 2025)
This study investigates the impact of foreign exchange rate fluctuations on the financial performance of KDB Bank Uzbekistan from 2019 to the third quarter of 2024. Using a quantitative approach, the research analyzes net profit, foreign exchange gains and losses, and annual average USD/UZS and EUR/UZS exchange rates. Descriptive statistics reveal that depreciation of the Uzbek soum was accompanied by increased volatility in bank profitability. Correlation analysis shows a strong positive relationship between FX gains and net profit (r = 0.92), and a negative correlation with FX losses (r = –0.80). An OLS regression model explains 64.1% of the variance in profitability, highlighting the sensitivity of bank earnings to exchange rate changes, particularly against the US dollar. The findings emphasize the importance of foreign exchange risk management in Uzbekistan’s banking sector and offer practical insights for policymakers and financial institutions operating in volatile currency environments.